The Yoik Opens Secret Doors to Sami Oral Literature: A Path into Language, Identity and Self-Esteem - Hirvonen, Vuokku (Sámi dieđalaš áigečála, 2026)
Since the founding of the Sami University College, our students have been able to study the Sami language and Sami literature as separate subjects. One of the main themes of the literature education has been the study of the Sami oral tradition of yoiking – or chanting – because yoiking lies at the core of Sami culture, as well as being an important skill which requires a great deal of knowledge. Through oral literature, we can tell where we came from and share our personal histories and identities as well as the histories of our communities – and attain collective integrity. The oral tradition reflects that which is important for us, and, through language, we express our own world view and values. This world view has grown from our surroundings and from the connection we have with nature and all living creatures. Thus, this paper focuses on how we can use oral indigenous literature in learning our language, strengthening our selfesteem and building up a positive identity.